2022
DOI: 10.1021/acs.jpcc.2c00742
|View full text |Cite
|
Sign up to set email alerts
|

Isostructural MFM-300(Sc) and MFM-300(In): Adsorption Behavior to Determine Their Differences

Abstract: and MFM-300(In) are isostructural materials that experimentally exhibit similar benzene adsorption properties with a higher capture value for MFM-300(Sc). This difference is explained in this report with a theoretical study. Intermolecular interactions are analyzed with the electron density functional theory, using Quantum Theory of Atoms in Molecules (QTAIM) and Non-Covalent Interactions index (NCI). Theoretical results indicate the establishment of two interactions between the benzene molecule and two μ 2 -O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Another example of chemical confined systems is with Metal-Organic Structures (MOF). These systems have many atoms, and the adsorption of some molecules inside the MOFs is one of the main applications of these materials [71][72][73][74][75][76][77][78][79] In these systems, the characterization of the MOF-guest interactions is relevant. For example, the interaction of CO molecule with the MOF named InOF-1 was characterized by using the GPUAM code.…”
Section: Chemical Confinementmentioning
confidence: 99%
“…Another example of chemical confined systems is with Metal-Organic Structures (MOF). These systems have many atoms, and the adsorption of some molecules inside the MOFs is one of the main applications of these materials [71][72][73][74][75][76][77][78][79] In these systems, the characterization of the MOF-guest interactions is relevant. For example, the interaction of CO molecule with the MOF named InOF-1 was characterized by using the GPUAM code.…”
Section: Chemical Confinementmentioning
confidence: 99%
“…Vargas et al , 125 studied the adsorption capacity of benzene on MFM-300(Sc) and MFM-300(In) with adsorption isotherms from 0 to 0.85 P / P 0 at 298 K, obtaining 4.8 mmol g −1 of capture for MFM-300(Sc), which was slightly higher than that for MFM-300(In) of 3.5 mmol g −1 . DFT simulations indicated that the benzene molecule forms stable interactions in both MOFs, Bz@MFM-300(M), with formation energies of −84.09 kJ mol −1 for MFM-300(Sc) and −97.07 kJ mol −1 for MFM-300(In).…”
Section: Gas/vapour Capture and Separationmentioning
confidence: 99%